Microsoft PowerPoint 2002 fast & easy - Witherspoon, Coletta (Prima Pub. RosedaleUS, 2001)
Offers step-by-step guidelines and tips for creating and delivering informative and effective presentations. Includes instructions for organizing the presentation outline, shaping up presentation slides, customising the presentation, inserting graphics, using digital photographs, incorporating tables, printing and delivering the presentation; and publishing it on the Web.